The Relationship Between Profitability and Bankruptcy Assessment Based on Lis’s Four-Factor Model. Case Study of the Alcoholic Beverage Company - Grigoryan, Liana; Grigoryan, Ani (ՀՀ ԳԱԱ)
In the article, we researched the key indicators of Diageo Corporation, aiming to identify the most risky trends. For the study the chosen time lag was the trend of the last 10 years. Diageo is a part of the beverage industry. Its business involves the supply of alcoholic beverage under a collection of brands such as Johnnie Walker, Crown Royal, Buchanan’s and Windsor whiskies, Smirnoff, Cîroc and Ketel One vodkas. Diageo’s dividend grew at a compound annual rate of almost 6%, which is far ahead of inflation and more than enough the most income investors to keep happy. Using methodological assessment, we assessed the profitability of the company, for which we identified return on equity, economic profitability, and net return on assets. Taking into account the analysis conducted and the indicators recorded during the assessment, we considered it essential to assess the company’s bankruptcy risk. For this purpose, we used the bankruptcy risk assessment method by R. Liss, which is widely used in international practice. The assessment recorded as a result of the model implementation is perceived as a safe financial situation for the company. Հոդվածում ուսումնասիրել ենք Դիագեո կորպորացիայի հիմնական ֆինանսական ցուցանիշները՝ նպատակ ունենալով բացահայտել ամենառիսկային միտումները: Հետազոտության համար ընտրված ժամանակային լագ է համարվել վերջին 10 տարվա միտումը: Դիագեո կորպորացիան խմիչքների արդյունաբերության մի մասն է: Վերջինիս բիզնեսը ներառում է ալկոհոլային խմիչքների մատակարարում այնպիսի ապրանքանիշերի հավաքածուի ներքո, ինչպիսիք են՝ “Johnnie Walker”, “Crown Royal”, “Buchanan’s” և “Windsor” վիսկիները, “Smirnoff”, “Ciroc” և “Ketel One”օղիները: Միայն 2024 թվականի առաջին կիսամյակում ընկերության շահաբաժինն աճել է գրեթե 6 տոկոսով, ինչը ոչ միայն խոստումնալից ցուցանիշ է, այլև ներդրողների տեսանկյունից գրավիչ։ Հոդվածում, մեթոդական գնահատման միջոցով, գնահատել ենք ընկերության շահութաբերությունը, որի համար վերլուծել ենք սեփական կապիտալի եկամտաբերությունը, տնտեսական շահութաբերությունը ևակտիվների զուտ եկամտաբերությունը: Հաշվի առնելով իրականացված վերլուծության պատկերը և գնահատման ընթացքում արձանագրված ցուցանիշները, առանցքային ենք համարել ընկերության սնանկության ռիսկի գնահատման անհրաժեշտությունը: Այդ նպատակով օգտագործել ենք միջազգային պրակտիկայում լայն կիրառություն գտած Ռ. Լիսի սնանկության ռիսկի գնահատման մոդելը: Մոդելի տեղայանացման արդյունքում արձանագրված գնահատականն ընկերության համար ընկալվում է անվտանգ ֆինանսական իրավիճակ:
Keywords: Economics